2021
DOI: 10.1093/ckj/sfab210
|View full text |Cite
|
Sign up to set email alerts
|

Use of nephrotoxic medications in adults with chronic kidney disease in Swedish and US routine care

Abstract: Background To characterize use of nephrotoxic medications in patients with CKD Stage G3-5 in routine care. Methods Cohorts of adults with confirmed CKD G3-5 undergoing routine care during January 1, 2016 through December 31, 2018 in two health systems (Stockholm CREAtinine Measurements [SCREAM], Stockholm, Sweden [N = 57,880]; and Geisinger, Pennsylvania, U.S. [N = 16,255]). We evaluated the proportion of patients receiving n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 46 publications
0
28
2
Order By: Relevance
“…They observed that 9% of older adults with CKD stage 3 and 38% with CKD stage 4 received at least one contraindicated drug. Bosi et al [51] expanded this work by evaluating the risk of nephrotoxic drug use by persons with eGFR <60 ml/min/1.73 m 2 during the more recent period 2016-2018. The situation proved to be similar or worse; during a 1-year period, 20% of patients with CKD received at least one potentially inappropriate nephrotoxic medication.…”
Section: Drug Safety Effectiveness and Monitoringmentioning
confidence: 99%
“…They observed that 9% of older adults with CKD stage 3 and 38% with CKD stage 4 received at least one contraindicated drug. Bosi et al [51] expanded this work by evaluating the risk of nephrotoxic drug use by persons with eGFR <60 ml/min/1.73 m 2 during the more recent period 2016-2018. The situation proved to be similar or worse; during a 1-year period, 20% of patients with CKD received at least one potentially inappropriate nephrotoxic medication.…”
Section: Drug Safety Effectiveness and Monitoringmentioning
confidence: 99%
“…3 ). 16 , 17 Thus, only 23% of participants in the CKD cohort had been diagnosed by their physicians as having CKD while the number should be 100%.
Fig.
…”
Section: Chronic Kidney Disease: An Evolving Concept Not Well Known O...mentioning
confidence: 99%
“…Note that among persons included in the cohort because researchers retrospectively diagnosed CKD, the physician in charge diagnosed cancer or diabetes more commonly than CKD. Data from 16 , figure from 17 . …”
Section: Chronic Kidney Disease: An Evolving Concept Not Well Known O...mentioning
confidence: 99%
“…Indeed, GFR and UACR thresholds to define CKD were chosen because, when persisting for ˃3 months, they are associated with an increased risk of adverse outcomes including acute kidney injury (AKI), progression to kidney failure requiring kidney replacement therapy, and all-cause mortality. Despite the clear implications of a CKD diagnosis for health, and clear-cut diagnostic criteria, CKD remains an unrecognized condition, especially in older adults [ 5 ]. Moreover, recognition of CKD is important for adequate drug prescription.…”
Section: Introductionmentioning
confidence: 99%